Economic Activities in Urban Settlement Public Spaces: Behavior as an Identity - Ima Rahmawati Sushanti; Purwanita Setijanti; Dewi Septanti (Journal of Architecture & Environment, 2022)
Behavior aspects cover response of interaction between human and places, showing existence of interactive spaces that not only describes behavior but also the place character. Currently, the level of need for human social and economic interaction is increasingly binding. Purpose of this study is to identify behavior of users in public space especially in utilizing space when they carry out social and economic activities simultaneously, and to question whether the creation of public space can reflect the character of identity. Activities to be observed are in residential corridor of Sekarbela, Mataram City. This space is used daily as space for social and economic interaction. This is qualitative research using grounded theory and case study. Data collection techniques were carried out by observation, description, and documentation. Interactive analysis model is used with descriptive analysis of behavior setting in Sekarbela corridor. The results show that social and economic activities are behavior identities in public space of urban settlement. The routine activities of production, distribution, and consumption in this area unwittingly make this space unified and give more meaning to a public space; not only perceived social and economic space separately but intertwined each other and makes the public space more vibrant.